Optimal Deployment Schedule for Vibration Reduction of Lift-Offset Coaxial Rotorcraft using Individual Blade Control - Hong, S.H.; Kim, D.K.; Jung, S.N. (My University, 2023)
This study investigates the optimal vibration reduction using the IBC (Individual Blade Control) actuation concept for a coaxial lift-offset (L.O.) rotorcraft in high-speed cruise flight. The rotorcraft vibration analysis model consists of a three-bladed coaxial rotor and a one-dimensional (1D) finite element (FE) fuselage stick model. A 1D FE stick model of the fuselage is constructed based on the natural frequency data of XH-59A and several other conventional helicopters. A total of 14 free vibrating modes are used to describe the airframe motions, after conducting a convergence study on the vibration behavior of the vehicle. The rotor-body vibration analysis is carried out using either one-way or two-way coupled method, and the results are validated with XH-59A flight test data. The two-way coupled predictions show relatively good correlations with the flight test data. The active vibration reduction gains obtained at the rotor hub and the pilot-seat via various actuation scenarios are examined. The IBC actuation is demonstrated to be very effective in reducing the vibration levels at both the locations of the vehicle. A multi-harmonic IBC actuation schedule enables to suppress the overall vehicle vibration by 80.6%, as compared to the baseline uncontrolled case.
Keywords: Dynamics